Integrated modelling of DEMO-FNS current ramp-up scenario and steady-state regime. (30th April 2015) - Dnestrovskij, A.Yu.; Kuteev, B.V.; Bykov, A.S.; Ivanov, A.A.; Lukash, V.E.; Medvedev, S.Yu.; Sergeev, V.Yu.; Sychugov, D.Yu.; Khayrutdinov, R.R.
Abstract: An approach to the integrated modelling of plasma regimes in the projected neutron source DEMO-FNS based on different codes is developed. The consistency check of the steady-state regime is carried out, namely, the possibility of the plasma current ramp-up, acceptance of growth rates of MHD modes in the steady-state regime, heat loads to the wall and divertor plates and neutron yield value. The following codes are employed for the integrated modelling. ASTRA transport code for calculation of plasma parameters in the steady-state regime, NUBEAM Monte Carlo code for NBI incorporated into the ASTRA code, DINA free boundary equilibrium and evolution code, SPIDER free boundary equilibrium and equilibrium reconstruction code, KINX ideal MHD stability code, TOKSTAB rigid shift vertical stability code, edge and divertor plasma B2SOLPS5.2 code and Semi-analytic Hybrid Model (SHM) code for self-consistent description of the core, edge and divertor plasmas based on the experimental scaling laws. The consistent steady-state regime for the DEMO-FNS plasma and the plasma current ramp-up scenario are developed using the integrated modelling approach. Passive copper coils are suggested to reduce the plasma vertical instability growth rate to below ∼30 s −1 .The outer divertor operation in the 'high-recycling' regime is numerically demonstrated with a maximal heat flux density of 7–9 MW m −2 that is technically acceptable.